AKUNTANSI FORENSIK SEBAGAI STRATEGI PEMBERANTASAN KORUPSI SUAP - Bambang Arianto (FKIP, Universitas Banten Jaya, 2021)
This article aims to elaborate on the role of forensic accounting as a strategy to eradicate the criminal practicebribery in Indonesia. Forensic accounting can be used as a step to strengthen evidence by trying to collectvarious pieces of evidence through investigations into bribery corrupt practices. Forensic accounting is ascheme developed as a preventive, detective and persuasive strategy through the application of investigativeaudit procedures that are litigation for decision making in court. Thus, forensic accounting can be used as astrategy in an effort to eradicate the criminal practice of bribery corruption. This article uses the literaturestudy method by elaborating various findings on the role of forensic accounting through a variety of literatureboth journals and newsletters. This article argues that the role of forensic accounting has made a positivecontribution as a strategy in efforts to eradicate bribery corruption in Indonesia.